Asymptotic Methods in the Probabilistic Analysis of Sequencing and Packing Heuristics - Coffman, E. G.; Lueker, G. S.; Rinnooy Kan, A. H. G. (Management Science, 1988)
Recently there has been considerable interest in the average-case performance of heuristics. This paper pursues that interest, where it concerns sequencing and packing problems. In particular, we survey the methods that have been used to obtain formal probabilistic analyses of heuristics for makespan scheduling and one-dimensional bin packing. In so doing, we present many of the key results in these research areas.